2021
DOI: 10.1038/s41598-020-80317-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, infection intensity and geographical distribution of schistosomiasis among pre-school and school aged children in villages surrounding Lake Nyasa, Tanzania

Abstract: Planning and implementation of schistosomiasis control activities requires an understanding of the prevalence, intensity of infection and geographical distribution of the disease in different epidemiological settings. Although, Tanzania is known to be highly endemic to schistosomiasis, there is paucity of data on the geographical distribution of schistosomiasis in potential large water bodies in the country. Thus, the present study was conducted to determine the prevalence, infection intensities and geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
5
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
4
19
5
1
Order By: Relevance
“…This suggests that all age groups are equally active in their water contact behaviour in the area. In contrast to our finding, students aged 10 to 14 years are at higher risk of schistosomiasis than students below 10 years of age as reported elsewhere [ 46 , 49 , 50 ]. This might be linked with the high frequency of bathing and swimming habits of schoolchildren of older ages.…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests that all age groups are equally active in their water contact behaviour in the area. In contrast to our finding, students aged 10 to 14 years are at higher risk of schistosomiasis than students below 10 years of age as reported elsewhere [ 46 , 49 , 50 ]. This might be linked with the high frequency of bathing and swimming habits of schoolchildren of older ages.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of urogenital schistosomiasis in this study increased as the age groups of the children increased attributed to early exposure to infested water which results in the acquisition of the disease at an early age with peak prevalence and intensity concentrated in the 6 to 17 years. The present findings are consistent with the other studies reported in Tanzania and Nigeria [ 23 , 24 ]. Also, there was a statistically significant variation of urogenital schistosomiasis prevalence among the schools with the highest prevalence in Longa Primary School (60.9%) followed by Nyengedi (55.9%) and Nyangamara (32.9%) Primary Schools.…”
Section: Discussionsupporting
confidence: 94%
“…The current finding, on S. mansoni infection prevalence, was also lower than those reported at 41.3% from western Kenya ( 31 ), 64.3% from Northwestern Tanzania ( 32 ), and 58.1% from western Côte d'Ivoire ( 33 ).…”
Section: Discussioncontrasting
confidence: 86%